Management of Dystocia due to Fetal Ascites in a Non-Descript Doe - Manivannan, Nivetha; Rasool, Akhter; Thulasiraman, Sarath; Rangaswamy, Baranidharan Govindaswamy; Narayanasamy, Arunmozhi (The Indian Journal of Animal Reproduction, 2025)
Fetal ascites, characterized by an abnormal accumulation of fluid in the fetal peritoneal cavity, is a rare but significant cause of dystocia in small ruminants. The present paper describes successful management of dystocia due to fetal ascites in a four-year-old pluriparous non-descript doe using minimally invasive obstetrical procedure i.e., puncture of the fetal abdomen to reduce its size and facilitate per-vaginal delivery which was effectively utilized as an alternative approach to cesarean section. This approach minimized risks and ensured favorable outcomes. Routine antenatal ultrasonographic monitoring is recommended to detect fetal anomalies early and optimize the management of high-risk pregnancies in small ruminants.